MAJĀZ IN ARABIC AND PASHTO: A COMPARATIVE STUDY IN LIGHT OF THE INFLUENCE OF ARABIC RHETORIC: AL-MAJĀZ BAYNA AL-‘ARABIYYAH WA AL-BASHTŪWIYYAH: DIRĀSAH MUQĀRANAH FĪ ḌAW’I AL-TA’ATHTHUR BI AL-BALĀGHAH AL-‘ARABIYYAH - Ismail Shinwari; Abdullah Nuri; Najibullah Jamal Arif; Faqir Sayyid Hashimi; St. Fauziya (Muaddib: Journal of Arabic Language and Literature, 2026)
This study explores majāz (figurative language) in Arabic and Pashto, focusing on its conceptualization, classification, and usage. As a central element in balāghah (rhetoric), majāz functions to convey meanings beyond literal interpretation. This research aims to examine the similarities and differences between the two languages while identifying the influence of Arabic rhetorical tradition on Pashto. Using a qualitative descriptive-comparative approach based on library research, the study analyzes data from classical Arabic rhetorical works and Pashto linguistic literature. The findings indicate that both languages share a similar definition of majāz as a word used beyond its original meaning with a contextual indicator (qarīnah) preventing literal interpretation. Moreover, both traditions classify majāz into comparable categories, particularly istiʿārah (metaphor) and majāz mursal (metonymy). However, minor differences are observed in stylistic usage and contextual application. The study further reveals that Pashto rhetoric is significantly influenced by Arabic balāghah, especially in conceptual frameworks and classification systems. Thus, the relationship between the two is not merely one of similarity, but also of intellectual influence and conceptual transfer.